1998
DOI: 10.1177/001872679805100501
|View full text |Cite
|
Sign up to set email alerts
|

Individualism/Collectivism Orientations and Reactions Toward Alternative Human Resource Management Practices

Abstract: In this study, we examined the relationship between individualism-collectivism orientations of potential job seekers and their reactions toward alternative human resource management (HRM) practices in the areas of selection, performance appraisal, reward system, career system, and employment security. Using several subdimensions of individualism-collectivism, we found many significant relationships between individualism-collectivism orientations and preferences for alternative human resource management practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
160
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(174 citation statements)
references
References 9 publications
10
160
0
2
Order By: Relevance
“…COL was negatively related to preferences for individualbased pay in the US (Cable and Judge, 1994) and to the use of selection tests, formal appraisal practices, and desire for promotions based on merit, and positively related to preference for equality-based rewards and employment security among US business undergraduates (Ramamoorthy and Carroll, 1998). Both COL and PD interacted with feedback type such that US subjects' performance increased as a result of both positive and negative feedback, but in England (where COL and IND were significantly higher), only positive feedback resulted in performance increases (Earley, 1986).…”
Section: Hrm (5)mentioning
confidence: 98%
“…COL was negatively related to preferences for individualbased pay in the US (Cable and Judge, 1994) and to the use of selection tests, formal appraisal practices, and desire for promotions based on merit, and positively related to preference for equality-based rewards and employment security among US business undergraduates (Ramamoorthy and Carroll, 1998). Both COL and PD interacted with feedback type such that US subjects' performance increased as a result of both positive and negative feedback, but in England (where COL and IND were significantly higher), only positive feedback resulted in performance increases (Earley, 1986).…”
Section: Hrm (5)mentioning
confidence: 98%
“…Ramamoorthy and Carroll (1998) maintain that collectivism encourages cooperation, whereas individualism is driven by competitiveness. Because collectivist individuals prefer teamwork and encourage cooperation, while individualists tend to cooperate less in group activities (Wagner, 1995), collectivism should be positively associated with the SSC.…”
Section: Career Values and Collectivismmentioning
confidence: 99%
“…Ramamoorthy et al's (2007Ramamoorthy et al's ( : 1999 study shows that Indian employees during the 2003-2004 period reported low tenure intent and a high level of commitment. Second, an alternative explanation could be the fact that in a collectivist culture such as India, individuals subordinate their personal goals for the sake of the organization regardless of their level of attachment to the organization (Ramamoorthy & Carroll, 1998;Saini & Budhwar, 2008). Ramamoorthy et al (2007) note that employees in India are bounded by the social perimeter of their groups (Ramamoorthy & Flood, 2002) and the relationship between an employee and the organization extends beyond One plausible explanation is that individuals who do not have better options outside the organization may stay loyal to the organization out of necessity rather than desire or sense of obligation.…”
Section: Insert Tables 3 and 4 Around Here Hypotheses Testingmentioning
confidence: 99%